Putting Jesus in his place : the case for the deity of Christ - Bowman, Robert M; Komoszewski, J. Ed (Grand Rapids, MI : Kregel Publications, 2007)
"Putting Jesus in His place" demonstrates that the New Testament--from beginning to end--clearly reveals Jesus' divine identity. What's more, it shows that belief in Jesus as God was the conviction of his original Jewish followers, rooted in Old Testament theology and in what Jesus himself said and did
Includes bibliographical references and index
Keywords: Jesus Christ -- Divinity